2013
DOI: 10.1007/s11746-013-2205-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Hydrolysis of Sacha Inchi Oil using Conventional and Supercritical Carbon Dioxide Processes

Abstract: Sacha inchi (Plukenetia volubilis) oil has high polyunsaturated fatty acids content. The hydrolysis of this oil is an efficient way to obtain desirable free fatty acids (FFA). The optimization of parameters was carried out according to the maximum production of FFA using two enzymatic hydrolysis processes. The effect of enzyme concentration (5-40 % based on weight of oil), temperature (40-60°C), and oil:water molar ratio (1:5-1:70) were studied for the conventional enzymatic hydrolysis process, while pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…These results showed that enough water is necessary for the hydrolysis of Phoenix tree seed oil. Similar effect of water on the lipase-catalyzed hydrolysis of oil can also be found in previous reports (Chen et al, 2014;Prado and Saldaña, 2013).…”
Section: Effect Of Mass Ratio Of Water To Oilsupporting
confidence: 88%
See 1 more Smart Citation
“…These results showed that enough water is necessary for the hydrolysis of Phoenix tree seed oil. Similar effect of water on the lipase-catalyzed hydrolysis of oil can also be found in previous reports (Chen et al, 2014;Prado and Saldaña, 2013).…”
Section: Effect Of Mass Ratio Of Water To Oilsupporting
confidence: 88%
“…To evaluate the effect of the reaction temperature on the hydrolysis of Phoenix tree seed oil, experiments were performed at different temperatures from (Prado and Saldaña, 2013), which was attributed to the difference in hydrolysis media.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…Although this conventional method produces high conversion yield, it requires high temperature (100–260 °C) and pressure (100–7000 kPa), thus causing undesirable reactions such as dehydration, oxidation of fatty acids, and interesterification of triglyceride . Oil hydrolysis using lipase as a biocatalyst has received considerable attention for the production of fatty acids . This method is more advantageous than the conventional method because the method can be employed at low temperatures and demonstrates high selectivity, thus leading to energy conservation and obtaining high‐purity products .…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Oil hydrolysis using lipase as a biocatalyst has received considerable attention for the production of fatty acids. [16][17][18] This method is more advantageous than the conventional method because the method can be employed at low temperatures and demonstrates high selectivity, thus leading to energy conservation and obtaining high-purity products. 17,19,20 In addition, the use of lipase for oil hydrolysis guarantees a contamination-free product, which is the primary concern in food technology, cosmetics, and biomedical applications, because consumers prefer natural compounds or those that are identical to natural compounds rather than chemically synthetic products.…”
Section: Introductionmentioning
confidence: 99%
“…Sacha inchi oil has high content of unsaturated fatty acids, mainly linoleic acid, and a-linolenic acid. These fatty acids are essential fatty acids, which mean that humans cannot synthesize them and they should be acquired from the diet (Prado & Saldaña, 2013). Its oil contain more than 90% of unsaturated fatty acids including:42-48% linolenic acid (x-3), 32-37% linoleic acid (x-6), and 9-12% oleic acid (x-9) (Chirinos, Pedreschi, Domínguez, & Campos, 2015a;Follegatti-Romero, Piantino, Grimaldi, & Cabral, 2009); the ratio of 0.76:1 for omega-6:omega-3 is good for human health (Prado et al, 2011).…”
Section: Introductionmentioning
confidence: 99%